MMPs and TIMPs expression in facial tissue of children with cleft lip and palate - Smane-Filipova, Liene; Pilmane, Mara; Akota, Ilze (Biomedical papers of the Medical Faculty of the University Palacký, Olomouc Czech Republic, 2016)
BACKGROUND AND AIMS: Morphogenesis of the upper lip and palate is a complex process involving highly regulated interactions between epithelial and mesenchymal cells. Genetic evidence in humans and mice indicates the involvement of matrix metalloproteinases (MMPs) and their endogenous tissue inhibitors (TIMPs) in cleft lip palate (CLP) aetiology. This study investigated whether expression of MMP-2, MMP-8, MMP-9, TIMP-2, and TIMP-4, which are essential for the upper lip and palate fusion, is dysregulated in children with CLP. METHODS: Oral mucosa tissue samples were obtained from patients with complete unilateral (CU) CLP (n = 25) and complete bilateral (CB) CLP (n = 19) during corrective plastic surgery and in unaffected control subjects (n = 10). MMPs and TIMPs expression was assessed by immunohistochemistry, and the data were analyzed using the Kruskal - Wallis test with the Bonferroni correction. RESULTS: In CLP patients, MMP-2, TIMP-2 immunoreactivity in the oral mucosa was seen to have a few to abundant structures, but the overall number of MMP-2, TIMP-2-positive structures was greater than that in controls (P < 0.01). The total number of TIMP-4, MMP-9-positive cells showed a significant decrease in the CBCLP compared with that of CUCLP (P < 0.001). MMP-8 expression trends in the CLP group were similar to those of the control group. CONCLUSIONS: The results suggest that TIMP-4 and MMP-9 are the main ECM remodeling regulatory proteins expressed in CUCLP affected tissues of the oral mucosa. The increased expression of MMP-2 and TIMP-2 in CLP tissues implicates these factors in the regulation of cell migration during ECM turnover independently of different types of clefts. Investigation of MMP and TIMP expression in tissue samples from patients with CLP appears to be a promising approach to the etiopathogenesis of CLP.
Keywords: Cleft Lip; Humans; dítě; Extracellular Matrix; Child; obličej; Female; Matrix Metalloproteinases; tkáňové inhibitory metaloproteinas; extracelulární matrix; lidé; předškolní dítě; ústní sliznice; matrixové metaloproteinasy; ženské pohlaví; Male; Tissue Inhibitor of Metalloproteinases; Cleft Palate; rozštěp patra; Mouth Mucosa; rozštěp rtu; Face; mužské pohlaví; Child, Preschool